Wear Particles in the Hydraulic System and Their Impact on the Gear Pump Efficiency - Novak, Nejc; Trajkovski, Ana; Bartolj, Jan; Majdič, Franc (International Conference Fluid Power 2025: Conference Proceedings, 2025)
Wear particles in hydraulics accelerate the wear of elements in a gear pump. The contact between the gear and the pump housing is particularly exposed to wear. With an increase in the amount of particles in the oil, the volumetric efficiency of the pump deteriorates rapidly in the aforementioned contact and the useful life of the pump is thus reduced. The paper shows the calculation of the concentration of wear particles in the oil according to the ISO 4406 standard using the example of 20/19/18. Adding wear particles and sustainable testing at different concentrations affect the rate of decrease in the volumetric efficiency of gear pumps when increasing the concentration of particles in the oil.